2014
DOI: 10.1097/sle.0b013e3182a2b03e
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hand-assisted Laparoscopic Surgery Using Tissue Fusion Devices and Open Resection for Treatment of Rectosigmoid Carcinoma

Abstract: Modern tissue fusion devices used in hand-assisted laparoscopic surgery (HALS), a method of combining endoscopic surgery with tactile sensation, can minimize surgical trauma and hospitalization times beyond both conventional laparoscopy and open surgery. The outcomes of HALS using tissue fusion devices and conventional open surgery for curative resection of rectosigmoid carcinoma were compared. A total of 78 (45 males, 33 females; mean age, 57.2±11.7 y) rectosigmoid carcinoma patients underwent HALS surgery (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The scores of methodological quality assessment of the enrolled retrospective studies were shown in Table 2 and the scores of randomized controlled trial were shown in Table 3 . Of those 15 articles, 11 retrospective studies [ 23 28 , 31 34 , 37 ] had fair quality (8–14 scores). Three randomized controlled trial [ 30 , 35 , 36 ] had low quality (all were 2 scores).…”
Section: Resultsmentioning
confidence: 99%
“…The scores of methodological quality assessment of the enrolled retrospective studies were shown in Table 2 and the scores of randomized controlled trial were shown in Table 3 . Of those 15 articles, 11 retrospective studies [ 23 28 , 31 34 , 37 ] had fair quality (8–14 scores). Three randomized controlled trial [ 30 , 35 , 36 ] had low quality (all were 2 scores).…”
Section: Resultsmentioning
confidence: 99%